Brain stimulation and computerized working memory training on language recovery in people with aphasia - Kranou-Economidou, Despina (Department of Rehabilitation Sciences, Faculty of Health Sciences, Cyprus Universtiy of Technology, 2020)
Conventionally, aphasia, the language disorder following brain damage which is frequently accompanied by deficits of working memory (WM), is treated with traditional language therapy to improve receptive and expressive language skills. Many times, though improvement of language abilities for people with aphasia (PWA) is slow, and PWA end up in rehabilitation programs for long periods of time with a big economic burden and a slow improvement. As technology is improving though, it is essential for research to look into other ways to support aphasia rehabilitation. The modern technology of non-invasive brain stimulation equipment, the Transcranial Magnetic Stimulation (TMS) and a well-established computerized cognitive training program, RehaCom, were used as a joint treatment method to facilitate language recovery, and in turn have a positive effect on quality of life (QoL). The treatment reported in this thesis is the first to be used in PWA. The specific goals were to investigate whether the application of excitatory TMS to the left dorsolateral prefrontal cortex (LDLPFC) followed by computerized WM training lead to near-transfer on WM tasks and non-verbal intelligence, and far-transfer on language tasks, narratives, functional communication and QoL. Although the results revealed a mixed and indistinct pattern of training and transfer effects across participants this treatment showed a positive effect in neurorehabilitation of PWA. While all participants showed improvements in cognitive and linguistic tasks, the most noteworthy observation was that two of the participants with global aphasia significantly improved in non-verbal intelligence and three participants showed a modest improvement in the WM screening task, specifically in the number of correct responses. Overall findings showed a significant trend for improvement and a significant difference between the treated and untreated periods in non-verbal intelligence, accompanied with significant and non-significant trend for improvement in language abilities. The treatment results are encouraging, and it is clinically and theoretically important to further investigate whether this treatment will be taken on as an innovative method for post-stroke aphasia rehabilitation in the future and convert it from an efficacious to an efficient treatment in the clinical setting to improve language functions.
Keywords: Aphasia; Language; Working memory; TMS; Non-verbal intelligence